Kinematic versus Mechanically Aligned Total Knee Arthroplasty: A Meta-analysis of Randomized Controlled Trials - Boutros, Marc; Awad, Guy; Mouawad, Adeline; Mansour, Elie (The Journal of Knee Surgery, 2025)
Alignment strategy in total knee arthroplasty (TKA) remains a subject of debate. Although mechanical alignment (MA) has long been the standard, kinematic alignment (KA) has gained interest for its patient-specific approach aiming to restore native knee kinematics. Comparative evidence from randomized controlled trials (RCTs) on clinical effectiveness and safety remains variable. A systematic search of PubMed, Scopus, Cochrane Library, and Google Scholar through June 2025 identified 21 RCTs comparing KA and MA in primary TKA. Outcomes assessed included functional scores (Knee Society Score [KSS], Oxford Knee Score [OKS], KOOS, WOMAC), quality of life (EQ-5D, Forgotten Joint Score [FJS]), pain (VAS at rest and mobilization), range of motion, satisfaction, and complications rates. KA was associated with modestly better outcomes in early postoperative function and patient satisfaction. Statistically significant advantages were found for knee flexion (MD = 2.49 degrees; p = 0.002), KSS function (MD = 6.39; p < 0.00001), KSS objective score (MD = 2.24; p < 0.00001), KSS satisfaction (MD = 3.11; p = 0.001), FJS (MD = 3.79; p < 0.0001), WOMAC (MD = –6.44; p = 0.01), and VAS pain at rest (MD = –0.39; p < 0.0001). No significant differences were observed in extension, pain during mobilization, length of stay, or complication rates. Kinematic alignment yields clinical outcomes at least equivalent to mechanical alignment, with small but statistically significant improvements in early function, joint awareness, and patient satisfaction, without increased risk of complications or revision. Although the clinical relevance of these differences is modest, KA represents a safe and effective alternative that may enhance patient-perceived recovery. Long-term data remain essential to determine whether KA offers durable advantages in survivorship and late functional outcomes.
Keywords: total knee arthroplasty; kinematic alignment; mechanical alignment